Ženska kot grešni kozel - Zaviršek, Darja (Ars et humanitas, 2018)
The article analyses the phenomenon of neopatriarchy, as the continuation of classical patriarchy in neoliberal conditions. It shows that transnational neoliberalism is linked with the neoliberal masculinism, which appears as neopatriarchy and intends to answer the problems of global economic inequalities: the shortage of the jobs; the increased need for care work; ecological catastrophes and mass migrations. Instead of focusing on these issues, women have become scapegoats and are seen as guilty for societal crises. In order to discipline them, repatriarchalisation and retraditionalisation by political leaders have increased as well as by the winners and losers of the transnational neoliberalism, who use religious and nationalist ideologies to control women. The formation of neopatriarchy in post-socialist countries and in Western countries is diverse; the analysis of the different phenomena carried out in this study, from the media representations, political programmes, films and everyday normalisation of violence, show its varied appearances.
Keywords: nasilje; neoliberalism; neoliberalizem; neopatriarchy; neopatriarhat; postsocialism; postsocializem; transnacionalni hegemonski maskulinizem; transnational hegemonic masculinism; violence